Aquaponic biofilter system using heliconia sp. for ammonia removal in lake - Miswan, Muhammad Safwan (2020)
Lakes are considered as one of the natural water resources in Malaysia. The quick pace of development around many lakes catchment areas has a significant impact on water quality. Consequently, biofilter aquaponic system for ammoniacal nitrogen removal in lake near non-point sources such as oil palm plantation, factory and educational building were studied. Aquaponic is a system that mutually integrates aquaculture and plant cultivation. Aquaponic biofilter system also applies phytoremediation mechanism to reduce nutrient. Therefore, phytoremediation of lake water in Tasik Teknologi in campus area of Universiti Tun Hussein Onn Malaysia (UTHM) was performed in 7 days by using Heliconia sp. as phytoremediate plant. This study was conducted in a greenhouse experiment to control the environments conditions (with different temperature and photoperiod), which consists of five hydroponic tanks, and one fish culture tank with the 40 watt of water pump was run circulation of water. A physicochemical characteristic of Tasik Teknologi was compared to Interim National Water Quality Standard Malaysia (NWQSM) after phytoremediation. Heliconia sp. after phytoremediation was undergoes analysis for plant nutrients by using Ion Chromatography (IC) in three major parts; leaves, roots and stem. The result shows that Tasik Teknologi has mean values of AN (3.95 mg/L), NO2 (0.12 mg/L), NO3 (1.36 mg/L), BOD (105.70 mg/L), COD (10.30 mg/L), TSS (19.70 mg/L), Turbidity (12.30 mg/L), temperature (28.80oC), DO (9.40 mg/L) and pH (6.51), respectively. Phytoremediation has reduced AN and NO3 from the lake water sample by Heliconia sp. with 66.00% and 92.03% removal efficiency, respectively. Besides that, the concentration of DO during phytoremediation was increased 47.82 % from 2.4 mg/L to 4.6 mg/L. Furthermore, the uptake of AN in three major parts of Heliconia sp. leaves, stem and root were found to be 4.40 %, 1.12% and 4.20%, respectively. The Heliconia sp. has the ability in reducing AN and NO3 in lake water with efficiently and practically.